CONTRASTIVE ANALYSIS OF ENGLISH AND INDONESIAN NOUN ARTICLES - I Wayan Mulyawan (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2014)
Almost in all languages, there are terms of countable and uncountable nouns. In order to apply the noun, it should be preceded with an article. The articles that use in each language are different. This research is aimed to find out the different between English and Indonesia noun articles and to elicit which one has the most simple and/or complete. The problems discussed are : how do the articles used ?; what are the differences and similarities ? The discussion shows that the aplication of noun articles should be followed such as the nouns category/shape, the first letter of the nouns, the plural/singular form, etc.; the English article is more simple than the Indonesian article. Keywords: noun articles, countable and uncountable noun.